Harvesting energy from flood mitigation ponds using water wheel - Din, Abdul Talib; Yaakob, Mohd Yuhazri; Othman, Mohd Yazid (2011)
Flood mitigation pond is a compulsory landscape structure that the developer needs to provide to comply with the Malaysia Building by Laws. Normally flood mitigation ponds in a housing estate or any land development are located at different elevation and connected to each other by a cascade flume. The flow of water in this cascade flume is capable of generating sufficient power for landscape lighting or aerators to treat the pond water. Aeration in the pond water is very important in order to create conducive living environment for the flora and fauna in the pond. The research was carried out by installing a water wheel at the cascade flume to tap the potential energy from the head different of the water flowing in-between the two ponds. The water wheel uses both kinetic energy of the water jet created in a specially designed pipe end and also by means of the weight of water accumulated in the fiberglass buckets fixed at the perimeter of the wheel. Two 200mm diameter PVC pipe installed leading to the wheel bucket for this purpose. If there is heavy rain, the storm water will quickly fill up the pond thus create a huge flow rate of water in the 200mm diameter in one of the tapping pipe and produce a powerful jet at the pipe nozzle to push the scoop beside the bucket. At the same time the water in the other 200mm diameter PVC pipe fill up the buckets to move the bucket downward by gravity. The water wheel size is 10 meter diameter and supported by two pillars made of welded carbon steel pipe trusses. The rotation of wheel is enhanced by the inertia force due to the self weight of the wheel and the weight of water accumulated in the bucket, transmitted to a 1:600 speed multiplication system using gear and V belt. Once the bucket which is filled with water reached the bottom of the wheel, it will immediately discharge the water into the lower pond thus lessen the weight of the bucket for upwards movement to the top of the wheel. This process will go on until the wheel turn at a sufficient torque and rpm to generate electrical energy which then transferred to the battery bank located at the footing of the wheel structure. The electrical energy from the battery is used to light up the garden lighting and aerator machine in the ponds by means of inverter which converts the dc current to ac current. The wheel could be further improved in term of torque and rpm by reducing friction at the rotating shaft bearings and also by aerodynamic shape of the buckets and other rotating structures to reduce air resistance.